2006
DOI: 10.1007/s10439-006-9091-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Material Properties with Tissue Composition in Enzymatically Digested Bovine Annulus Fibrosus and Nucleus Pulposus Tissue

Abstract: Aging and degeneration of the intervertebral disk are accompanied by decreases in water and proteoglycan contents, and structural alterations. The aim of this study was to determine the impact of compositional changes on the material properties of intervertebral disk tissues. Confined compression stress-relaxation experiments were applied to bovine caudal annulus fibrosus and nucleus pulposus tissue specimens that were separated into three experimental groups: in situ, free-swelling control (PBS), and digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 32 publications
14
75
2
Order By: Relevance
“…Specifically, studies have shown hypermobility at low loads 34 and altered viscoelastic properties including increased creep rate and deformation 35 in early degeneration, mechanical changes that are attributed to the reduction in nucleus glycosaminoglycan. 5,7,8,36 At 4 weeks postinjection, neutral zone modulus, range of motion, and creep were all altered in a manner consistent with the expected changes in a degenerating disc, and were altered to the same degree as observed after an equivalent ChABC injection in vitro. Further, both neutral zone modulus and range of motion were linearly correlated with nucleus glycosaminoglycan content 4 weeks postinjection-relationships that were identical to those determined in the absence of biologic activity.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 54%
See 1 more Smart Citation
“…Specifically, studies have shown hypermobility at low loads 34 and altered viscoelastic properties including increased creep rate and deformation 35 in early degeneration, mechanical changes that are attributed to the reduction in nucleus glycosaminoglycan. 5,7,8,36 At 4 weeks postinjection, neutral zone modulus, range of motion, and creep were all altered in a manner consistent with the expected changes in a degenerating disc, and were altered to the same degree as observed after an equivalent ChABC injection in vitro. Further, both neutral zone modulus and range of motion were linearly correlated with nucleus glycosaminoglycan content 4 weeks postinjection-relationships that were identical to those determined in the absence of biologic activity.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 54%
“…[2][3][4] This reduction of glycosaminoglycan content has an impact on the mechanical function of the disc: the ability to imbibe and bind water is diminished, pressure within the nucleus is decreased, and ultimately, the mechanical function of the nucleus and the entire motion segment is altered. [5][6][7][8] It is plausible that progressive degeneration follows this reduced glycosaminoglycan content and altered mechanics, yet this ultimately remains a hypothesis, and knowledge of specific mechanisms and interactions is limited. To this end, in vivo animal models simulating the condition of decreased nucleus pulposus glycosaminoglycan content as observed in early degeneration would be of great utility.…”
mentioning
confidence: 99%
“…Recent years have seen a multitude of studies focusing on the analysis of changes in the extracellular matrix of the IVD during ageing [4,5,7,13,14,15,16,17,18]. However, despite tremendous research efforts, we still lack knowledge regarding cell density and GAG content throughout the IVD.…”
Section: Discussionmentioning
confidence: 99%
“…The youngest specimen in our study came from a 19-year-old person. This prevented us from analyzing how cell density and GAG content change during the years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) when the IVD and the endplates undergo the greatest changes.…”
Section: Glycosaminoglycans In the Intervertebral Discs And The Endplmentioning
confidence: 99%
See 1 more Smart Citation